Computer performance evaluation and benchmarking : SPEC Benchmark Workshop 2009, Austin, TX, USA, January 25, 2009 : proceedings - Kaeli, David (Springer, 2017)
his book constitutes the proceedings of the SPEC Benchmark Workshop 2009 held in Austin, Texas, USA on January 25th, 2009.